Effect of Aloe Vera mouthwash on moderate gingivitis: Clinical and microbiological study - Lana Slewa Ishaq; Amal Hanna Aziz (Erbil Dental Journal)
Background and objectives: Gingivitis is an inflammatory process confined to the gingiva with no attachment or bone loss, Aloe Vera (AV) is an ancient medicinal plant that is widely known for its medicinal uses. This study was planned to assess the effect of AV as a mouthwash on clinical periodontal parameters; plaque index (PI), gingival index (GI) and bleeding index (BI) and to evaluate its antibacterial effect on bacterial plaque Staphylococcus Aureus and Streptococcus Viridans, comparing it with chlorhexidine (CHX) mouthwash.